Impaired Spatial Category Representations in Williams Syndrome; an Investigation of the Mechanistic Contributions of Non-verbal Cognition and Spatial Language Performance - Farran, Emily K.; Atkinson, Lauren; Broadbent, Hannah (Frontiers in Psychology, 2016)
The aims of this study were to: provide a precise characterisation of spatial category representations in Williams syndrome (WS); to determine the nature of the mechanistic contributions from spatial language performance and non-verbal cognition to spatial category representations in WS; and to explore the stability of spatial category representations in WS using error analysis. Spatial category representation was assessed across nine spatial categories (In, On, Under, In Front, Behind, Above, Below, Left and Right) using an odd-one-out task. The performance of individuals with WS (N=24; 12;00 years; months to 30;07 years; months) was compared to data from typically developing children aged four to seven years (N=75), published in Farran & Atkinson (2016). The WS group performed at the level of typical 4- and 5-year-olds. Despite this low level of ability, they demonstrated typical variation in their representation of easier to harder spatial categories, in line with the spatial category representation model (Farran & Atkinson, 2016). Error analysis of broad category understanding (i.e. category understanding which includes non-prototypical category members), however, showed that errors reflected fewer guess responses than expected by chance in the WS group only, which could suggest strategic responding in this group. Developmental trajectory analyses demonstrated a significant contributing influence of both non-verbal mental age and spatial language in the TD group. For the WS group, non-verbal mental age significantly contributed to spatial category representations, whilst the contributing influence of spatial language ability was marginally significant. With reference to level of ability, spatial category representations in the WS group were consistently lower than would be expected for non-verbal mental age, but on a par with their (low) spatial language mental age. Spatial category representations in WS are discussed with reference to their contribution to the hallmark deficit in spatial construction and drawing abilities in WS.